WADASAN AS AN ARCHITECTURAL ELEMENT IN GUA SUNYARAGI WATER PARK, CIREBON - W. S. (Jurnal Riset Arsitektur, 2019)
Abstract- Taman Air Gua Sunyaragi was established for The Sultan Cirebon and family to meditate and recreation. The purpose of this research is to know the use of Wadasan at Taman Air Gua Sunyaragi and its availability in Cirebon at this time. This research aims to maintain existence of Wadasan at Taman Air Gua Sunyaragi also existence of Wadasan in Cirebon.This research used three theories, theory of function from Schulz, theory of semiotic from Charles Jencks and atmosphere from Peter Zumthor. The method used is qualitative, comparative and descriptive with architectural approach (function) and material. Data collection was done by interview technique and direct observation in the study case.Architecture of Taman Air Gua Sunyaragi compared by Java-The Middle East-Chinese styles. Taman Air Gua Sunyaragi consists of elements, stone, brick, water and vegetation likes landscape of Chinese Water park. The sacred atmosphere within the complex is created by using Wadasan. Wadasan has an architectural function as a building envelope, circulation barrier and sculpture. Wadasan combined by water serves as temperature controller to reduce the ambient temperature. The stone used as Wadasan has a variety of types but has the same character. Some Wadasan’s materials is hard to find in Cirebon, but can be replaced with a race on the character Wadasan. Function of water park in Taman Air Gua Sunyaragi can’t run properly because of the loss of water element. Wadasan treatment at Taman Air Gua Sunyaragi is done by attaching the loose rocks and providing water with high pressure to remove moss. Key Words: Sunyaragi, Water Park, Wadasan, Character, Rocks